2011
DOI: 10.2486/indhealth.ms1197
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Morbidity Induced by Occupational Inhalation Exposure to Formaldehyde

Abstract: The potential of formaldehyde to produce chronic respiratory tract disease remains a controversial issue. The main purpose of this study was to investigate the respiratory effects, if any, of long term occupational exposure to formaldehyde. This cross-sectional study was carried out at a local melamine-formaldehyde resin producing plant. The study population consisted of seventy exposed and 24 non-exposed (referent) employees. Using respiratory questionnaire, data on respiratory symptoms were gathered. Atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 9 publications
3
14
0
Order By: Relevance
“…Kriebel et al found that among students in the anatomy dissection laboratory, exposure to 1.1 ppm formaldehyde for 2.5 h/wk reduced the peak expiratory flow (PEF) by 1% per ppm [22]. Neghab et al also observed that long-term occupational exposure to formaldehyde was associated with impaired lung function, as evidenced by decreased vital capacity (VC), forced vital capacity (FVC) and forced expiratory volume in the first second (FEV 1 ) [23]. Consistent with these human studies, the results of our animal studies indicated that FA exposure significantly increased the airway resistance during inspiration and expiration in non-sensitized BALB/c and C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Kriebel et al found that among students in the anatomy dissection laboratory, exposure to 1.1 ppm formaldehyde for 2.5 h/wk reduced the peak expiratory flow (PEF) by 1% per ppm [22]. Neghab et al also observed that long-term occupational exposure to formaldehyde was associated with impaired lung function, as evidenced by decreased vital capacity (VC), forced vital capacity (FVC) and forced expiratory volume in the first second (FEV 1 ) [23]. Consistent with these human studies, the results of our animal studies indicated that FA exposure significantly increased the airway resistance during inspiration and expiration in non-sensitized BALB/c and C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have only focused on the effect of air formaldehyde exposure on respiratory and dermal health due to the unknown health impact of melamine (Supplemental Table 9). [12][13][14][15][16][17] Ours is the first study to comprehensively examine the exposure assessment of melamine and its health effect in the occupational setting. Two prior studies only measured ambient melamine exposure either from one laboratory chamber or from the field with different exposure sources.…”
Section: Discussionmentioning
confidence: 99%
“…11 Some previous occupational epidemiologic studies have found that melamine-formaldehyde resin-related workers suffered from respiratory and dermal adverse health effects, probably due to ambient formaldehyde exposure. [12][13][14] In contrast, no one has examined the effect of melamine exposure on early renal injury in the same workplace. Thus we designed time-series and cross-sectional studies in melamine tableware manufacturing factories to investigate whether melamine exposure causes early renal injury by measuring several candidate markers for glomerular and renal tubular functions.…”
mentioning
confidence: 99%
“…This makes it unsuitable for use in in vitro microleakage and bond strength research. [ 24 25 ] Formalin is a skin and eyes irritant,[ 10 ] cytotoxic, genotoxic,[ 28 ] and carcinogenic. [ 29 ] Therefore, although being an efficient sterilization method, its use is discontinued as it poses a major health hazard.…”
Section: Discussionmentioning
confidence: 99%